The Impact of Head Room Leadership Style on Motivation and Performance of Implementing Nurses (A Literature Review - Agustin, Leni; Riskika, Siti; Wardani, Hamidah Retno (Universitas Bondowoso, 2023)
Introduction: In nursing, leadership is the use of the skills of a leader (nurse) in influencing other nurses who are under his supervision for the division of tasks and responsibilities in providing nursing care services so that nursing goals are achieved (Latif, 2008). Leadership behavior will be reflected in the leadership style that appears when leading his subordinates. In influencing the performance of subordinates, an effective leadership style is needed. The purpose of this study is to review some of the literature that contains the leadership style of the head of the room that can improve and optimize the motivation and performance of nurses in hospitals as an effort to improve the quality of nursing services. Method: Literature search strategy through Google schoolar using several keywords, namely